La partecipazione dei rappresentanti della nazione italiana all’Insurrezione polacca di Gennaio 1863–1865. Genesi, storia, commemorazione .......... 39 - Kłaczyński, Robert (Riflessioni intorno alla storia politica d’Italia = Refleksje wokół historii politycznej Włoch, 2025)
THE PARTICIPATION OF REPRESENTATIVES OF THE ITALIAN NATION IN THE POLISH ARMED UPRISING OF 1863–1865: ORIGINS, HISTORY, COMMEMORATIONThis article addresses issues crucial to the history of international relations, which, despite the passage of over 160 years, continue to have a clear positive impact on Polish- Italian relations. The January Uprising (1863–1865) was one of the most important events shaping Poles’ attitudes in the years following the “partitions of Poland” The Uprising has received widespread coverage in the European press, focusing the elites’ attention. This resulted in an influx of volunteers into the insurgent ranks from almost all European countries. The largest group was made up of Italians, whose fates were strongly intertwined with Poland’s aspirations to regain independence. Many of them paid with their lives or captivity for their heroic stance, thus sharing the fate of the Polish insurgents. The Polish-Italian brotherhood in arms has endured to this day, and the memory of the 1863 events is still cherished today by numerous monuments and the names of streets, squares, and parks.